Evaluation of a Trauma Service: Patient and Family Perspectives. Issue 4 (July 2020) - Wake, Elizabeth; Battistella, Tania; Dale, Kate; Scott, Matthew; Nelson, Renee; Marshall, Andrea P.
Abstract : Background: Patient satisfaction is an indicator of the quality of care that underpins a patient's health care experience. A focus on both the patient and the family is important when evaluating satisfaction from the perspective of patients with trauma and is consistent with delivery of patient- and family-centered care. Using the literature to guide development, we designed and implemented a questionnaire to evaluate attitudes and experiences of patients and families case managed by the trauma service. This article reports the findings of this quality improvement project. Methods: A cross-sectional cohort pragmatic design was used. The questionnaire was conducted with 142 trauma patients and 49 family members. Data included hospital admission data, application of a satisfaction tool, and free text comments. Results: Both patients and their family members rated the trauma service highly in the satisfaction scoring. Differences in the communication practices encountered by patients and families were identified. Conclusions: Strategies to involve family members and promote family-centered care are required in the context of trauma patients to improve the safety, quality, and satisfaction of the care they receive while being managed by the trauma service. Abstract : Supplemental Digital Content is Available in the Text.